Imágenes de la Prisión en tiempo de guerra, 1812, 1912, 2012 - Zozaya-Montes, Maria (2013)
Nowadays, the history of the prisoners of Napoleonic wars has been deformed on the collective imaginary of the common people. We study the three basic moments for the creation of that image. Firstly: 1808-1814, the experience in the French prison of the Spanish lieutenants and non-commissioned officers. At least, as we show studying the material conditions, that experience was not so terrible as people use to think between elite prisoners. But it was spread the idea that it was very hard, or at last no one spoke about it. That situation requires a main reason: to had a “normal life” on the country of the “French enemies” was punished by the Spanish authorities after the war (1814). Secondly, 1908-1912, the period for which are presented the photos of the caserne where those prisoners lived in, caserne which was one of the best of all France, as we consider. Thirdly, 2008-2012, when we examine -backwards- all that combination, then we can explain the motives for the big gap that exist on that period and the black legend which has covered it.